Titanium implant can promote M2 polarization with macrophages activation which contribute to osteogenesis and angiogenesis via inactivates JAKS signaling pathway - Xiao Luo; Lin Xiao (BMC Immunology)
Abstract Implants can regulate the phenotypic transformation of macrophages from pro-inflammatory M1-type to anti-inflammatory M2-type, and macrophage polarization plays an important role in the process of osteogenesis and angiogenesis. This study aims to explore the potential mechanism of the regulation of macrophage polarization by titanium implants. Macrophages were treated with lipopolysaccharide (LPS) and IFN-γ to induce inflammatory microenvironment in vitro. Markers of M1 and polarization levels were evaluated. Then the conditioned culture medium collected from macrophages were used for periodontal ligament stem cells (PDLSCs) and human umbilical vein endothelial cells (HUVECs) culture. The angiogenesis capacity of HUVECs and osteogenic differentiation capacity of PDLSCs were then evaluated. Moreover, the changes in levels of inflammatory cytokines obtained by the Raybiotech cytokine antibody chip, and the potential regulatory signaling pathway was investigated. Titanium implant promoted the activation of M2-type macrophages to enhance angiogenesis of HUVECs and osteogenic differentiation of PDLSCs. Then the western blotting analysis suggested that IL-6/JAK2/STAT3 signaling pathway was inacticated in macrophages attached to titanium implant. The coumermycin A1, a JAK2 agonist, significantly weakened the regulatory role of titanium implant on macrophages polarization and subsequent effects on angiogenesis of HUVECs and osteogenic differentiation of PDLSCs. Taken together, macrophages of M2 type can be stimulated by titanium implant in vitro, and this stimulation promotes the osteogenic differentiation of PDLSCs and angiogenesis in HUVECs through inactivation of JAK2/STAT3 signaling pathway.